IMPLEMENTASI SCIENTIFIC LEARNING UNTUK MELATIH HIGHER ORDER THINKING SKILL (HOTS) PESERTA DIDIK - Siti Mariyam (Jurnal Guru Dikmen dan Diksus, 2020)
Scientific Learning (SL) helps students observe and imitate any solutions that arise in their groups when they face a problem. SL can also balance the ability of students with the process of assimilation, accommodating problems, developing strategies and finding relationships for each event to solve problems. The SL learning model will produce competencies such as persistence, Student self-control, open thinking through discussion, flexible in making decisions, reasoning to choose the best solution, creative and thinking critically to find solutions where all are the abilities needed to train the HOTS competences of Students. The research was conducted in 3 cycles with 6 learning meetings on the subject of Number Processing / Spreadsheet Applications in class X Accounting at SMK Muhammadiyah Aimas, Sorong Regency. The data analysis technique used triangulation techniques both data and methods from the results of interviews recording, storing visual data, and telephone recordings. The results showed that SL can increase students' HOTS which is marked by increasing high-level thinking competencies including critical thinking, problem solving, adaptability, high initiative, creativity, curiosity to solve problems which are entirely of the students' individual ability. Meanwhile, in terms of social skills, it is marked by improving the communication and collaboration skills of students in solving problems.